The critical role of primary care clinicians in the early detection of ocular surface squamous neoplasia - Leendert Dekker; Jan F. Olivier; Klaus von Pressentin (South African Family Practice)
Ocular surface squamous neoplasia (OSSN) encompasses a spectrum of conjunctival tumours and, while rare globally, is the most common ocular malignancy in sub-Saharan Africa. Its rising incidence, primarily driven by the human immunodeficiency virus (HIV) epidemic, presents significant challenges in clinical diagnosis, as these lesions often share characteristics with other conjunctival lesions. In South Africa, where risk factors such as HIV, human papillomavirus infection and excessive sun exposure are prevalent, primary care clinicians play a crucial role in identifying and referring cases for early intervention. Ocular surface squamous neoplasia is often the first indication of HIV in patients who are otherwise unaware of their status when they present to healthcare workers, making it essential for healthcare workers to screen for HIV and initiate antiretroviral therapy. Early recognition of at-risk patients and prompt referral of suspicious lesions are imperative to improve patient outcomes and prevent vision loss.